Acute protease supplementation effects on muscle damage and recovery across consecutive days of cycle racing. Issue 2 (17th February 2016) - Shing, Cecilia M.; Chong, Suzzen; Driller, Matthew W.; Fell, James W.
Abstract: Bromelain, a mixture of proteases obtained from pineapples, has been demonstrated to reduce exercise-induced muscle damage and inflammation, enhancing recovery. This investigation aimed to establish if markers of muscle damage and testosterone were influenced by acute bromelain supplementation in competitive cyclists taking part in a six-day cycle stage race. Fifteen highly trained cyclists [age: 22, = 1.2 years, height: 1.79, = 0.01 m, body mass: 68.69, = 1.97 kg] were supplemented with either bromelain (1000 mg·day −1 ) ( n = 8) or a placebo ( n = 7) across six days of competitive racing in a randomised, double-blind, placebo-controlled trial. Blood was collected from each cyclist on days one, three and six of racing and analysed for creatine kinase (CK), myoglobin, lactate dehydrogenase (LDH) and testosterone. CK activity ( P < 0.001, d = 17.4–18.8), LDH activity ( P < 0.004, d = 0.5–2.5) and myoglobin concentration ( P < 0.007, d = 3.4–4.8) were elevated from pre-race on days three and six of racing in both groups. Testosterone concentrations were significantly lower on the final day of racing ( P = 0.03, d = 1.3) and there was a trend for bromelain to maintain testosterone concentrations across the race period ( P = 0.05, d = 1.04–1.70) when compared to placebo. Fatigue rating was lower in the bromelain group on day four of racing ( P = 0.01). Consecutive days of competitive cycling were associated with increased markers of muscle damage and a reduction in circulating testosterone across the race period. Bromelain supplementation reduced subjective feelings of fatigue and was associated with a trend to maintain testosterone concentration.